(untitled) (Materiali di Estetica. Terza serie, 2023)
This paper discusses some logic and ontological difficulties within colour theory: whether colour is an objective or subjective property; the difference among surface, atmospheric, and volume colour; the fact that colour names are vague, because they do not denote definite objects, but ranges; the puzzling question of “achromatic” colours. After shortly outlining the philosophical implications of various colorimetric systems, I discuss three possible interpretations of Aristotle’s claim that properties such as colours are inseparable from individual substances.